ENHANCEMENT OF GUIDELINES FOR ADJUDICATING CRIMINAL CASES THROUGH RESTORATIVE JUSTICE IN COURT INSTITUTION - Dedi Putra; I Nyoman Nurjaya (CV. RADJA PUBLIKA, 2025)
This research aims to analyze guidelines for adjudicating criminal cases through restorative justice in offenses affecting victims, the categorization of drug offenses suitable for restorative justice adjudication, and verdict forms not yet covered in Supreme Court Regulation Number 1 of 2024 concerning Guidelines for Adjudicating Criminal Cases Based on Restorative Justice. This research employs normative legal analysis through conceptual, legislative, and case methodologies. The analysis concludes that the rule has not established criteria for adjudicating narcotics offenses. The principle of restorative justice pertains not just to crimes with discernible victims but also to victimless acts, such as drug-related crimes. Individuals impacted by substance abuse are entitled to medical and social rehabilitation, which may reinstate their autonomy from narcotics, in alignment with the ideals of restorative justice. The author also suggests including several types of verdicts, such as imposing penalties, mandating restitution to parents, granting exemptions from punishment, absolving individuals of all legal rights, and enforcing compliance with peace accords. The diversity of verdicts assists judges in selecting the appropriate form when administering a sentence to the defendant within the context of restorative justice.